La incorporación de la perspectiva de género en el juicio por jurados: un análisis a la luz de la reciente sanción de la ley 6451 de juicios por jurados de la Ciudad Autónoma de Buenos Aires - Guerrero, Maite (2021)
This work obtained first place in the Call for Lecciones y Ensayos Magazine and the Gender and Law Program for the Dossier "Violence and/or gender discrimination and/or sexual orientation". -- This paper will address the importance of including the gender perspective in litigation in jury trials in order to avoid the presence of gender stereotypes that are discriminatory and harmful to women. A brief review of the legislation in force in the country will be carried out, emphasizing the recent enactment of Law Nº 6451 on Trial by Juries in the City of Buenos Aires. Next, the ways in which the gender perspective can be introduced to traditional litigation will be analyzed, with special focus on the construction of the instructions to the jury and on the voir dire hearing